A novel high accuracy bandgap reference voltage source. Issue 4 (6th November 2017) - Wang, Songlin; Feng, Shuang; Wang, Hui; Yao, Yu; Mao, Jinhua; Lai, Xinquan
Abstract : Purpose: This paper aims to design a new bandgap reference circuit with complementary metal–oxide–semiconductor (CMOS) technology. Design/methodology/approach: Different from the conventional bandgap reference circuit with operational amplifiers, this design directly connects the two bases of the transistors with both the ends of the resistor. The transistor acts as an amplifier to amplify the change of voltage, which is convenient for the feedback regulation of low dropout regulator (LDO) regulator circuit, at last to realize the temperature control. In addition, introducing the depletion-type metal–oxide–semiconductor transistor and the transistor operating in the saturation region through the connection of the novel circuit structure makes a further improvement on the performance of the whole circuit. Findings: This design is base on the 0.18?m process of BCD, and the new bandgap reference circuit is verified. The results show that the circuit design not only is simple and novel but also can effectively improve the performance of the circuit. Bandgap voltage reference is an important module in integrated circuits and electronic systems. To improve the stability and performance of the whole circuit, simple structure of the bandgap reference voltage source is essential for a chip. Originality/value: This paper adopts a new circuit structure, which directly connects the two base voltages of the transistors with the resistor. And the transistor acts as an amplifier to amplify the change of voltage, which is convenient for the feedback regulation of LDO regulator circuit, at last to realize the temperature control.